A Trendy Approach to UK Inflation Dynamics. Issue Volume 89:Issue S1(2021)Supplement (2nd July 2019) - Forbes, Kristin; Kirkham, Lewis; Theodoridis, Konstantinos
Abstract : This paper focuses on the time series of UK inflation to isolate a low‐frequency and slow‐moving component (the trend) from deviations around this trend. This slow‐moving trend explains a substantial share of UK inflation dynamics. International prices are significantly correlated with the cyclical movements, and the exchange rate is significantly correlated with movements in the persistent trend. The significance of variables emphasized in standard models (i.e. slack and inflation expectations) varies, and the magnitude of their effects is smaller than for commodity prices and exchange rates. These results highlight the sensitivity of UK inflation to external events and provide guidance on how monetary policy should respond.